2005
DOI: 10.1681/asn.2005040426
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor Ccr2 Deficiency Reduces Renal Disease and Prolongs Survival in MRL/lpr Lupus-Prone Mice

Abstract: MRL/MpJ-Faslpr /J (MRL/lpr) mice represent a well-established mouse model of human systemic lupus erythematosus. MRL/lpr mice homozygous for the spontaneous lymphoproliferation mutation (lpr) are characterized by systemic autoimmunity, massive lymphadenopathy associated with proliferation of aberrant T cells, splenomegaly, hypergammaglobulinemia, arthritis, and fatal immune complex-mediated glomerulonephritis. It was reported previously that steady-state mRNA levels for the chemokine (C-C motif) receptor 2 (Cc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 50 publications
4
55
0
1
Order By: Relevance
“…Several published works have shown that CCR2 -/-mice are resistant to experimental autoimmune diseases, including the B cell-dominant lupus model [36,37]. These observations support our current findings and emphasize the importance of CCR2-CCL2 pathway in the development of autoimmunity.…”
Section: Discussionsupporting
confidence: 92%
“…Several published works have shown that CCR2 -/-mice are resistant to experimental autoimmune diseases, including the B cell-dominant lupus model [36,37]. These observations support our current findings and emphasize the importance of CCR2-CCL2 pathway in the development of autoimmunity.…”
Section: Discussionsupporting
confidence: 92%
“…24 The members of the chemokine family specifically direct different leukocyte subsets by distinct chemokine receptors into different renal compartments. 63 For example, the chemokine CCL2 recruits CCR2 + proinflammatory macrophages and T cells into the glomerulus and the tubulointerstitium, 64,65 whereas CCR1 + cells only recruit to the interstitial compartment and not to the glomerulus in LN. 66 Other leukocyte subsets involve other chemokines and chemokine receptors for their recruitment into the kidney.…”
Section: Intrarenal Pathogenic Mechanisms Of Lnmentioning
confidence: 99%
“…In this model, CCR2 has been reported to contribute to the progression of autoimmune kidney injury, followed by the decreased number of macrophage (Mφ) (14). However, the pathogenesis of MDSCs, especially focused on CCR2 signaling, remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%